Adobe AIR & PHP development - Bates, R. (Richard); Safari eBooks ([S.l.] : Virtual Training Co., 2009)
"Adobe AIR is a cross-platform, lightweight deployment environment based on Adobe's Flash Player. It combines the expressiveness of Flash with the familiarity and features of traditional desktop applications. Combined with the server-side power and flexibility of PHP, Adobe AIR applications are redefining Rich Internet Application (RIA) development. This course, by seasoned Flex/AIR and PHP integration specialist Richard Bates, is designed for PHP developers at all skill levels. Viewers will learn AIR fundamentals and advanced integration techniques using real-world applications and common feature-set requirements. Work files are included. To begin learning today, simply click on the movie links." --Resource description page.
Title from resource description page (viewed Aug. 3, 2011).
Presenter, Richard Bates.
Keywords: Adobe AIR; PHP (Computer program language); Web site development; Flex (Computer file); Application software -- Development; Electronic books